INTERFERENSI ALIH KODE BAHASA INDONESIA KE BAHASA ARAB DI KALANGAN SANTRI: PENYIMPANGAN STRUKTUR KALIMAT - Muhammad Arifin Ilham; Tatang (PT. CASA CENDEKIA MEDIA, 2025)
This study examines the phenomenon of code-switching interference in the structure of Arabic sentences among students at Pondok Pesantren X, West Java. Code-switching becomes an important aspect in the language learning process at the pesantren, but students often experience deviations in constructing correct sentence structures according to Arabic grammar. This study aims to identify the types of code-switching deviations that occur in the conversations of students and to uncover the factors contributing to these deviations. The research was conducted using a qualitative descriptive method through direct observation of the students' conversations. The research results show eight main deviations that often occur in sentence structure, such as the use of inappropriate phrases and the repetition of irrelevant words. These deviations are caused by several factors, including environmental pressure that requires students to communicate in Arabic even though they have not yet mastered its grammar. These findings indicate the importance of gradual and intensive grammar training so that students can apply Arabic more accurately and effectively in daily communication. This study is expected to contribute to the improvement of Arabic language teaching methods in the pesantren environment.